Pemanfaatan Citra Penginderaan Jauh dan Sistem Informasi Geografis untuk Pemetaan Daerah Rawan Demam Berdarah Dengue (Studi Kasus di Kecamatan Pangandaran Kabupaten Ciamis Provinsi Jawa Barat) - Andri Ruliansyah; Totok Gunawan; Sugeng Juwono M (Loka Litbang Kesehatan Pangandaran, 2011)
Abstract. Dengue hemorrhagic fever (DHF) are acute febrile diseases, found in tropical andsubtropical regions, caused by dengue virus of the genus Flavivirus, family Flaviviridae. Subdistrict Pangandaran is an area that is quite a sharp increase in his case. Ranging from nocases in the period 1998-2002 increased 1 case in 2003, 4 cases in 2004, 22 cases in 2005,35 cases in 2006, 10 cases in 2007, 12 cases in 2008, 14 cases in 2009 and 13 cases in 2010.The purpose of this study was to determine the ability of remote sensing imagery and GIS inthe determination of physical environmental factors for the mapping of areas prone to denguefever, dengue fever spreads are based on the distribution of cases, places, and timesfrom 2005 through to 2010 and determine the level of vulnerability to dengue based on environmentalvariables and incidence of DHF. This study is an observational research withcross sectional analysis approach. The results showed that the integration of remote sensingimagery and GIS to analyze the physical environmental risk factors associated with thespread of dengue include: land use, altitude, rainfall, area mosquito and fly larvae densityarea. Distribution pattern of dengue in the district during the last 6 years Pangandaran concentratedin the southern region of Pangandaran sub-district, the Pangandaran village,Pananjung and Babakan. Distribution of cases based on patient characteristics dominatedin the groups of children and adolescents, while based on gender, women are more exposedcases compared to male. Incidence of dengue fever occur each after a decline in rainfallfrom the previous month and decreased at the back there was an increase of rainfall. Zoninglevel of vulnerability to dengue were in the southern district of Pangandaran, the village ofPangandaran, Babakan, Pananjung, Wonoharjo and Most Sukahurip. Broad zone of highvulnerability areas in the Pangandaran sub-district DHF is 22.76 km2 (30.07%), wide areazone vulnerability is 46.16 km2 (60.99%) and broad zones of high vulnerability area 6.75km2 (8.94%).